Sistem Pengendalian Internal dalam Lingkungan Pemerintahan - Yunni Susanty (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2010)
Governmen Internal Control System (SPIP) is a process that is integratedo the actions and activities THAT carried out continuosly by the management and all employees, to provide reasonable assurance of achieving organizational objectives through effective and efficient, the reliability of financial reporting, security of state aset, and compliance with laws and regulations. SPIP is supported by the five elements of internal control of the control environment, risk assessment, control activities, information and communication and monitoring internal control followed by elements of an effective control environment